Existence of financial equilibria in continuous time with potentially complete markets - Frank Riedel; Frederik Herzberg (Bielefeld University, Institute of Mathematical Economics (IMW), 2010)
We prove that in smooth Markovian continuous-time economies with potentially complete asset markets, Radner equilibria with endogenously complete markets exist.
Keywords: D52; D53; G12; 330; Potentially complete market; Continuous-time financial; market; Radner equilibrium; Itô diffusion; Analytic transition density; Kapitalmarkttheorie; Gleichgewicht; Stochastischer Prozess; Unvollkommener Markt; Theorie